(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
The article lists Ukrainian titles of suprageneric taxa of bryophytes of Ukraine – families, orders, classes and divisions, as many of these taxa hadn’t got proper Ukrainian names. Ukrainian names was derived from from the names of the families (or root), that have been proposed recently (Boiko, 2015), and the corresponding suffixes and endings: for family name -ев(і), -єв(і), -ов(і), order -альн(і), class -опсид(и), division -офіт(и). The list of taxa of bryophytes according to modern mosses, alphabetical list of Ukrainian names suprageneric taxa of bryophytes and an alphabetical list of Latin names of suprageneric of bryophytes are given.